O roli gravitacii v technike pedalirovanija pri peredvizenii na velocipede - Romanov, N. S. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
Though biomechanics of cycling is a well-developed part of sport science, gravity was never considered as a primary force to be used in a powerful and efficient pedaling technique. The present article was written in an attempt to eliminate this gap.